The Influence of Broken Home on Social Behavior Deviant Students at SMP N 2 Payakumbuh - Hana Rifasya, Najla; Dodi Pasila Putra (BiCED Proceeding, 2024)
This research is motivated by several problems that the author found in grade VIII of SMP N 2 Payakumbuh. The interesting thing that the author sees is related to the deviant social behavior of students who are influenced by broken home families. A broken home is a family condition where the parents of a child are divorced or only one parent takes care of the child. Children who come from broken home families tend to have poor social interaction. This research is included in quantitative research with a regression approach. The research was conducted at SMP N 2 Payakumbuh Jl. Prof. Dr. Hamka No.22, Kaniang Bukik, North Payakumbuh District, Payakumbuh City, West Sumatra. The population in this study is all grade VIII students. The sampling technique is using total sampling. The instrument in this study uses a questionnaire. The results of the hypothesis test that Fcalculated as 9,682 whilethe F table was 4.06 meaning 9,682 > 4.06 that Ho was rejected and Ha was accepted, meaning that there was an Influence of Broken Home Families on Social Behavior at SMP N 2 Payakumbuh. The influence of broken home education on the social behavior of students at SMP N 2 Payakumbuh is 14% then the rest is influenced by other factors.